Ответ:
Пошаговое объяснение:
5)
6 :(1 4/5)=(3х+0,6) : 2,88
6*2,88=1 4/5 *(3х+0,6)
1 4/5=9/5=1,8
17,28=1,8(3х+0,6)
5,4х+1,08=17,28
5,4х=17,28-1,08
5,4х=16,2
х=16,2:5,4
х=3
6)
3/8:0,75=0,6 :(х-2,8)
3/8=0,375
0,375:0,75=0,6:(х-2,8)
0,75*0,6=0,375(х-2,8)
х-2,8=0,45:0,375
х-2,8=1,2
х=1,2+2,8
х=4
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Пошаговое объяснение:
5)
6 :(1 4/5)=(3х+0,6) : 2,88
6*2,88=1 4/5 *(3х+0,6)
1 4/5=9/5=1,8
17,28=1,8(3х+0,6)
5,4х+1,08=17,28
5,4х=17,28-1,08
5,4х=16,2
х=16,2:5,4
х=3
6)
3/8:0,75=0,6 :(х-2,8)
3/8=0,375
0,375:0,75=0,6:(х-2,8)
0,75*0,6=0,375(х-2,8)
х-2,8=0,45:0,375
х-2,8=1,2
х=1,2+2,8
х=4